2007
DOI: 10.1136/bjo.2006.112656
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in the normal human cornea: a laser scanning in vivo confocal microscopy study

Abstract: Using laser scanning in vivo confocal microscopy this study highlights a significant, and relatively linear, reduction in keratocyte and endothelial cell density with increasing subject age. Interestingly, corneal sub-basal nerve fibre density also significantly decreases with increasing age. In vivo laser scanning confocal microscopy provides a safe, non-invasive method for the establishment of normative data and assessment of alterations in human corneal microstructure following surgery or disease processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
148
4
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(185 citation statements)
references
References 27 publications
23
148
4
10
Order By: Relevance
“…Moreover, the morphology of corneal blood vessels has been well studied and described both in vivo and ex vivo, mainly in the last decade, by means of confocal microscopy [34][35][36] or other innovative techniques [37,38]. Our present results are in agreement with all these previous observations and add new evidence on the morphological development of corneal neovascularization.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the morphology of corneal blood vessels has been well studied and described both in vivo and ex vivo, mainly in the last decade, by means of confocal microscopy [34][35][36] or other innovative techniques [37,38]. Our present results are in agreement with all these previous observations and add new evidence on the morphological development of corneal neovascularization.…”
Section: Discussionsupporting
confidence: 83%
“…In some of the earlier studies, age had no significant effect on CCT (16)(17)(18)(19)(20)(21)(22). All these reports postulated that the number and race of the subjects, and differences in pachymeter instruments, might affect the results (10).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the densities of BECs in normal eyes were similar compared with previous reports. [15][16][17][18] There are no significant differences between normal eyes and injured eyes concerning the densities of BECs, at 3 months after injury, except those with grade IV injury. Our finding suggested that the densities of BECs might be relatively stable during the epithelial recovery after chemical injury.…”
Section: Discussionmentioning
confidence: 94%